Imaging Kayser-Fleischer Ring in Wilson Disease Using In Vivo Confocal Microscopy. Issue 3 (March 2019) - Zhao, Tantai; Fang, Zhixue; Tian, Jiao; Liu, Jia; Xiao, Yangyan; Li, Huiling; Chen, Baihua
Abstract : Purpose: This study analyzes images of Kayser–Fleischer (K-F) rings in patients with Wilson disease (WD) using in vivo confocal microscopy (IVCM) and explores whether IVCM can be a useful clinical tool in facilitating the diagnosis and characterization of K-F rings. Methods: One hundred four eyes of 52 patients with WD and K-F rings (K-F group) and 52 normal eyes of 52 age- and gender-matched control subjects (control group) were enrolled in the study. Both K-F and control groups consisted of 29 male patients and 23 female patients. IVCM imaging was performed, and images of the peripheral Descemet membrane were analyzed. Results: All patients in K-F group showed abnormal patterns in the peripheral Descemet membrane from IVCM images. These abnormalities can be generally divided into 3 types: patchy, stripy, and spotty patterns. Each patient may have a combination of these patterns, with patchy pattern being most prevalent (100%), whereas stripy and spotty patterns are present in 30% to 40% of the K-F rings. Notably, these patterns are not correlated with other systematic symptoms of WD. Conclusions: IVCM images can be used as an objective clinical diagnostic tool to facilitate the identification of K-F rings and the diagnosis of WD.